Closed-Form Analysis for NOMA with Randomly Deployed Users in Generalized Fading - Papanikolaou, Vasilis K.; Karagiannidis, George K.; Mitsiou, Nikos A.; Diamantoulakis, Panagiotis D. (IEEE Wireless Communications Letters, 2020)
In a pioneering work, Ding et al. presented an analytical framework for the performance on non-orthogonal multiple access (NOMA), In downlink cellular networks with randomly deployed users. However, the Involved Integrals are approximated through quadrature methods, where the accuracy depends on the number of terms In the summation and -most Importantly- these methods hide the Impact of the parameters on the system design. In this letter, we present a novel general closed-form expression for the outage probability of NOMA downlink In cellular networks with randomly deployed users, which can be used for any fading distribution and can reveal useful Insights for the system design. Finally, we utilize this formula to provide a closed-form analysis for the Important case of Nakagami- m fading.
Created from Fastlane, Scopus look-up
Keywords: generalized fading; Non-orthogonal multiple access (NOMA); outage probability; randomly deployed users